Devil in spring - Kleypas, Lisa (Kleypas, Lisa. Ravenels, 2017)
Most debutantes dream of finding husbands. Lady Pandora Ravenel has different plans. The ambitious young beauty would much rather stay at home and plot out her new board game business than take part in the London Season. But one night at a glittering society ball, she's ensnared in a scandal with a wickedly handsome stranger. After years of evading marital traps with ease, Gabriel, Lord St. Vincent, has finally been caught by a rebellious girl who couldn't be less suitable. In fact she wants nothing to do with him. But Gabriel finds the high-spirited Pandora irresistible. He'll do whatever it takes to possess her, even if their marriage of convenience turns out to be the devil's own bargain.